2011
DOI: 10.3941/jrcr.v5i2.634
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol sclerosis of a giant liver cyst following failed deroofings

Abstract: Percutaneous alcohol sclerotherapy for simple liver cysts is an established and safe procedure. We report alcohol ablation of a very large (5.5 liters) liver cyst that had failed laparoscopic deroofing procedures twice. The cyst responded to multisession alcohol sclerotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 5 publications
0
21
1
2
Order By: Relevance
“…Generally, the recrudescence of symptoms was determined in 16 patients (23%), namely all the patients in whom a cyst with the diameter exceeding 50% as compared to the initial size was imaged during observation. These values are slightly greater than those determined in the works describing the methods in which the obliterating medium was ethyl alcohol ( 4 , 5 , 12 , 13 , 17 ) . On the other hand, the adoption of various assessment criteria in these studies does not enable one to draw clear conclusions.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Generally, the recrudescence of symptoms was determined in 16 patients (23%), namely all the patients in whom a cyst with the diameter exceeding 50% as compared to the initial size was imaged during observation. These values are slightly greater than those determined in the works describing the methods in which the obliterating medium was ethyl alcohol ( 4 , 5 , 12 , 13 , 17 ) . On the other hand, the adoption of various assessment criteria in these studies does not enable one to draw clear conclusions.…”
Section: Discussioncontrasting
confidence: 59%
“…Symptoms almost never occur in the case of lesions below the size of 5 cm. An enlarging cyst may be the reason for hepatomegaly, local integument projection, the compression of bile ducts or even acute abdominal symptoms related to hemorrhage into the cyst or its rupture ( 1 , 2 , 4 ) .…”
Section: Introductionmentioning
confidence: 99%
“… 1 This occurs in 15–16% of patients with HCs. 6 Symptoms are nonspecific and may include abdominal pain, early satiety, nausea, or vomiting. 3 Patients may have a palpable mass or hepatomegaly on physical exam.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…A sclerosing agent, such as dehydrated alcohol or a tetracycline, is injected into the cystic cavity after complete aspiration of the contents. 6 It has been well documented as a simple and safe procedure. A multicenter study of 86 patients with HC greater than 5 cm found aspiration sclerotherapy to be highly efficacious.…”
Section: Managementmentioning
confidence: 99%
“…However, these agents can cause undesired adverse effects (AEs) such as abdominal pain, high fever, and alcoholic intoxication . In addition, fluid re‐accumulation after sclerotherapy using ethanol or minocycline has been reported . Therefore, identification of novel sclerosing agents other than ethanol and minocycline is desired.…”
Section: Introductionmentioning
confidence: 99%